Integration of ASEAN Capital Markets with Developed Countries: Spillover Analysis for the 2003-2019 Period - Juniarti Puspita Wulandari; Moch. Doddy Ariefianto (Universitas Mataram, 2022)
This study aims to determine the spillover effect on the ASEAN stock market, which is influenced by the turmoil of the world's financial stock market centres, namely the United States, Japan and the United Kingdom, and to determine the pattern of influence of financial centres on countries in ASEAN. The data used in this research is time series data. Then an analysis of each country index was carried out, which the author obtained from the 2003-2019 period, and then the author used it to find emerging markets that were influenced by developed countries. This study uses the Dynamic Conditional Correlation-Generalized Autoregressive Heteroscedatic Model (DCC-GARCH) so that it is possible to examine the transmission of volatility between two different stock markets together. Based on the research results, it was found that there was a spillover effect from financial centre countries to emerging market countries in ASEAN. Besides that, there is also a finding that the spillover effect between the stock market of financial centers and developing country markets has varying results in the observation period. The 2008 financial crisis, which stemmed from the US financial crisis, caused significant changes to the ASEAN-5 stock market. This can be seen from the increasing influence or spillover effect of the American stock market, namely the SP500 and FTSE100, the most significant impact during and after the 2008 crisis.